Analysis of the Effect of Manufacturing Industry on Indonesia's Economic Growth - Putri, Putri; Sumanto, Agus; Rahmawati, Farida (Journal of Business Management and Economic Development, 2023)
GDP is the amount of value added generated by all business units in a particular country, or is the sum of the value of final goods and services produced by all economic units. GDP at constant prices shows the added value of these goods and services calculated using prices prevailing in a particular year as a basis, which aims to determine economic growth from year to year. The targeted sector is the manufacturing sector of the 17 sectors in Indonesia with 16 subsectors in the manufacturing industry. The calculation of this research uses Location Quotient, Shift Share and Sectoral Typology methods. The results of this study with the LQ method show that the calculation of ADHK GDP has 10 base subsectors and 6 non-base sectors. It is known by Shift Share analysis that the average value of Pj and Dj in all subsectors has a negative value, but there are still subsectors that in some years between 2015-2019 have a positive value in supporting Indonesia's growth. The LQ calculation was developed using the Sectoral Typology method with the results of 10 subsectors with more than enough meaning that the sector is a basic sector with an average LQ> 1 and based on ADHK GDP its growth is slower than ADHB GDP, and its national growth includes fast growth